An assessment of the role of socio-economic, maternal and service utilization factors in increasing self-reported maternal complications in India - Pradeep Kumar; Shobhit Srivastava; Chanda Maurya; Preeti Dhillon (BMC, 2021)
Abstract Background Self-reported maternal complications are associated with maternal morbidity, deliveries by C-section, postpartum depression, and maternal death. Thus, it is necessary to examine the contribution of socio-demographic and maternal characteristics, as well as service utilization in the rising self-reporting of maternal complications (difficulty with daylight vision, convulsions, swelling of the legs, body or face, heavy vaginal bleeding or high fever) in India. The study aimed at examining the factors that have influenced the increasing prevalence of maternal complications between 2005-06 and 2015-16 in India. Methods Data from the two most recent rounds of the National Family Health Survey, which covered a sample of 36,850 and 190,898 women respectively who delivered in the last five years preceding the survey has been used. Logistic regression analysis was performed to carve out the factors which significantly contributed to maternal complications among women aged 15 - 49 years in India. With the help of the Fairlie decomposition technique, the study quantified the contribution of factors which influenced the changes in maternal complications in the period from 2005-06 to 2015-16. Results A significant increase was seen in the prevalence of maternal complications - from 43.6% to 53.7% between the years 2005-06 and 2015-16. About 21% of the increase could be explained by certain maternal, households level factors, service utilization and birth outcomes. For example, service utilization, in which 13% was attributed to the place of delivery and 6% to postnatal care, was the major contributor to the increase in maternal complications from 2005-06 to 2015-16). This was followed by individual-level factors like education (2%), body mass index (4%) and tobacco use,. It was also found that household-level factors like standard of living (-3.7%) and region (-1.4%), and birth weight contributed to the reduction of complications during the period. Conclusion The increase in the prevalence of maternal complications in India could be attributed mainly attributed to increase in reporting behavior, an outcome of increased utilization of maternal healthcare services, and increase in BMI. However, reduced prevalence of maternal complications can be attributed to the decrease in the prevalence of low-birth-weight babies and tobacco use among women in India.